Assessing the Impact of a High Impact Practice: Implementing a Criminal Justice Shared Learning Experience Using the True Crime Podcast Serial. Issue 4 (30th November 2021) - Wood, McKenzie; Breach, Stephanie Ritchie
Abstract: Common high-impact practices include a diverse menu of curricula. One practice growing in popularity is the shared learning experience. Shared learning is an extension of the learning community concept, designed to have a common theme prevail through several courses, assignments, or semesters. This study discusses the application of a shared learning experience using the renowned podcast Serial . Survey data collected from criminal justice students at a medium-sized community college provide information related to indicators of, and barriers to, participation, and perceptions of impact on education. Curriculum design and factors related to successful implementation of shared learning experiences will also be discussed.